Остров капитанов: сказочные повести / Софья Прокофьева - Прокофьева Софья Леонидовна (АСТ, 2008)
Экземпляры: С/а ДБ (20091211) / Инвентарный номер: 95688 / Цена: 168.41 / Авт.знак: П 80 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6